Development of an Integrated Social Media and Technology based Coaching Model for Developing Early Childhood Healthcare Competencies of Caregivers in Local Administration Organization Childcare Centers - Phattarasatjatum, Preeyada; Nillapun, Maream; Prachusilpa, Gunyadar; Vanichwatanavorachai, Siriwan (Journal of The Royal Thai Army Nurses, 2021)
The objectives of this research and development were: 1) to develop and seek for an efficiency of an integrated social media and Technology based coaching model for improvement on healthcare competency of early childhood caregivers and 2) to access an effectiveness of based coaching model by using embedded mixed methods research by the samplings of five caregivers and forty-two early childhood in five childcare centers. The research instrument is a form of coaching model including knowledge competency test, skill competency assessment, attitude competency questionnaire, attitude questionnaire towards based coaching model, lesson learned reports, early childhood health assessment book. Data was analyzed by using mean, standard deviation, dependent T-Test, growth score, repeated measure ANOVA, and content analysis. The results indicated that: (1) an integrated based coaching model consists of “5 P Model”; first P is Purpose, second P is Participation, third P is Procedure Design, fourth P is Practice, and fifth P is Performance Reflection which was developed and obtained an efficiency of E1/E2 80.50/84.50. (2) the effectiveness, after using an integrated based coaching model, revealed that: 2.1) the average score of knowledge competency is higher (p<.05). 2.2) the average score of skill competency is higher (p<.05). 2.3) the average score of attitude competency is higher (p<.05). 2.4) attitude towards coaching model obtained the highest score level. 2.5) improvement on skill competency had higher growth score. 2.6) early childhood health development had higher growth score. This research was utilized to improve the competencies of caregivers and good health of early childhood.